Legal Protection for Investee Company in Venture Capital Agreement in Indonesia - Sihabudin, Sihabudin (Brawijaya Law Journal, 2019)
Business and entrepreneurship are one of the fundamental and important factors in the economy of a nation. In Indonesia lending is being intensified to small and medium-sized companies that are unable to borrow capital from banks through the establishment of venture capital by the government. The existence and role of financial institutions in the form of venture capital in Indonesia is important to study, because it is a new institution that is starting to develop, which certainly has an influence on the development of the business world and legal institutions and institutions. The research method used is empirical juridical, which is qualitative by means of descriptive analysis. The results of the study are that although venture capital has not been based on clear legal aspects, in practice, venture capital activities are complemented by an agreement. Venture Capitalist has a stronger position on the investee company, while freedom of contract can only be applied well when both parties have the same position. However, venture capital tends to protect interest (capital) with special provisions, including its responsibilities. Therefore there is a need for a model and further regulation of the contents of the "standard venture capital agreement", especially the financing mechanism as well as its implementation instructions, so as to provide clearer, more complete and stronger implementation guidelines. A financing agreement made between a venture capital company and its partner company is based on a standard contract that requires supervision and protection to maintain balance. Measures of protection and supervision are through the basis of legislation, control carried out by the government, control carried out by judges (courts) and legal consultants and notaries.